Ethnobotany of Medicinal and Edible Plants of Tobelo Dalam Tribe in Aketajawe Lolobata National Park Area - Arham Yakub; Amin Setyo Leksono; Jati Batoro (Graduate Program, 2019)
This research aimed to find out local knowledge applied by the people of Tobelo Dalam tribe in the use of medicinal and edible plants. This research was carried out in Aketajawa Lolobata National Park at Aketajawe Block during April-June 2018. This research used a descriptive method through interviews and literature review. The selection of informants employed a snowball technique in which the main characteristics of the informants were the community leader, the traditional leader, and the community of the Tobelo Dalam Tribe. Data were analyzed using a qualitative analysis for data deepening on the ethnobotany study aspect based on the results of surveys and interviews obtained. The data were then analyzed using the Index of Cultural Significance (ICS) to determine the significance value of each plant species. The results showed that the number of plants used for treatment was 44 species dominated by those from the Malvaceae family such as achira or money tree (Pachira aquatica), cacao (Theobroma cacao), balacai or physic nut (Jatropha curcas L.) and dingo dingoto or climbing pandanus (Freycinetia sp). These plants are used for the treatment of mild wounds, allergic itching, postpartum and low stamina. Meanwhile, the number of edible plants often utilized by the people Tobelo Dalam Tribe was 7 species, covering Ipomoea batatas, Xanthosoma sp, Manihot utilisima, Oryza Sativa L., Metroxylon sagu, and Colocasia esculenta. These edible plants derived from 5 families dominated by Aracaceae (33%), Euphorbiaceae (17%), Convolvulaceae (17%), and Palmae (16%). The utilized parts of the edible plants were tubers and pith.Keywords: Ethnobotany, Food, Medicine, Plant, Tobelo